Tropomodulin3 is a novel Akt2 effector regulating insulin-stimulated GLUT4 exocytosis through cortical actin remodeling - Lim, Chun-Yan (Nat Commun, 2015)
Akt2 and its downstream effectors mediate insulin-stimulated GLUT4-storage vesicle (GSV) translocation and fusion with the plasma membrane (PM). Using mass spectrometry, we identify actin-capping protein Tropomodulin 3 (Tmod3) as an Akt2-interacting partner in 3T3-L1 adipocytes. We demonstrate that Tmod3 is phosphorylated at Ser71 on insulin-stimulated Akt2 activation, and Ser71 phosphorylation is required for insulin-stimulated GLUT4 PM insertion and glucose uptake. Phosphorylated Tmod3 regulates insulin-induced actin remodelling, an essential step for GSV fusion with the PM. Furthermore, the interaction of Tmod3 with its cognate tropomyosin partner, Tm5NM1 is necessary for GSV exocytosis and glucose uptake. Together these results establish Tmod3 as a novel Akt2 effector that mediates insulin-induced cortical actin remodelling and subsequent GLUT4 membrane insertion. Our findings suggest that defects in cytoskeletal remodelling may contribute to impaired GLUT4 exocytosis and glucose uptake.